Dietary effects of astaxanthin on gonadal development in female broodstock of Macrobrachium rosenbergii - Tao, Mingwei; Wei, Jie; de Cruz, Clement; Wang, Junyi; Du, Houkuan; Zhou, Hangxian; Xu, Qiyou (Elsevier B.V., 2025)
This study examines the effects of dietary astaxanthin on ovarian development and reproductive health in female Macrobrachium rosenbergii, a key aquaculture species. Five isonitrogenous and isolipidic diets with astaxanthin levels of 0, 27, 62, 140, and 310 mg/kg (AS0, AS27, AS62, AS140, AS310) were tested over 56 days. Weight gain and specific growth rates were significantly higher in AS27, AS62, and AS140 compared to AS0 (P < 0.05). Survival rates were significantly higher in AS62, AS140, and AS310 compared to AS0 and AS27 (P < 0.05). The AS62 group exhibited the highest gonadosomatic index and estradiol levels, while vitellogenin levels were elevated in AS62 and AS140 (P < 0.05). Testosterone was significantly higher in AS27 and AS62 compared to AS310 (P < 0.05). Oxidative stress indicators showed lower malondialdehyde levels and higher superoxide dismutase activity in AS62, with total antioxidant capacity peaking in AS140 (P < 0.05). Transcriptome analysis revealed upregulation of genes involved in the pentose phosphate pathway, glutathione metabolism, and ubiquinone/terpenoid-quinone biosynthesis in AS140. Specifically, genes such as g6pd, fbp, gpx, and anpep were significantly upregulated (P < 0.05). Optimal astaxanthin levels (114.30–165.14 mg/kg) enhanced gonadal development, antioxidant capacity, and sex hormone regulation. This study provides insights into the molecular pathways through which astaxanthin supports reproductive health in broodstock M. rosenbergii.